2020
DOI: 10.3844/ajavsp.2020.32.42
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Polymorphisms at Heat Shock Protein 90 Gene by High Resolution Melting Assays for Potential Heat Tolerance among Nigerian Zebu Cattle Breeds

Abstract: Heat Shock Protein (HSP) 90 gene is a member of HSPs subfamily that act as molecular chaperons whenever animals come under thermal stress. The genes fulfill essential roles of providing cellular protection, immune response, protein synthesis, protein folding and unfolding, protection from cellular stress, inhibitory apoptosis and adaptation. This study was designed to analyze polymorphisms of HSP 90 and to evaluate their influence on heat tolerance among selected Nigerian zebu. The polymorphisms were also used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Heat stress has become a significant issue in climate change because it directly impacts the adaptability and survivability of farm animals to thermal assault. The HSP genes such as HSP70 and HSP90 are members of HSPs subfamily (molecular chaperone families) known to be highly expressed under stressful environmental and physiological conditions [27]. This study analyzed the polymorphisms of the 5' UTR of the HSP70 gene in the seven cattle populations in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…Heat stress has become a significant issue in climate change because it directly impacts the adaptability and survivability of farm animals to thermal assault. The HSP genes such as HSP70 and HSP90 are members of HSPs subfamily (molecular chaperone families) known to be highly expressed under stressful environmental and physiological conditions [27]. This study analyzed the polymorphisms of the 5' UTR of the HSP70 gene in the seven cattle populations in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…Heat shock proteins are group of proteins induced by thermal assault/ heat shock either facultatively or constitutively animals and humans are exposed to assault of thermal conditions (Onasanya et al 2021). Single nucleotide polymorphisms of HSPs 70 and 90 genes have been extensively characterized among Nigerian breeds of cattle particularly White Fulani, Sokoto Gudali, Red Bororo and Ambala and it was reported that Nigerian cattle breeds at these loci are highly polymorphic and diverse where detected SNP genotypes were found to have positive biological functions on the thermotolerance potentials (Onasanya et al 2021;Onasanya et al 2020 a, b;Onasanya et al 2019). The most prominent members of this group are a class of functionally-related proteins that are involved in the folding and unfolding of other proteins (De-Maio, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Heat shock proteins are group of proteins induced by thermal assault/ heat shock either facultatively or constitutively animals and humans are exposed to assault of thermal conditions (Onasanya et al 2021). Single nucleotide polymorphisms of HSPs 70 and 90 genes have been extensively characterized among Nigerian breeds of cattle particularly White Fulani, Sokoto Gudali, Red Bororo and Ambala and it was reported that Nigerian cattle breeds at these loci are highly polymorphic and diverse where detected SNP genotypes were found to have positive biological functions on the thermotolerance potentials (Onasanya et al 2021;Onasanya et al 2020 a, b;Onasanya et al 2019). The most prominent members of this group are a class of functionally-related proteins that are involved in the folding and unfolding of other proteins (De-Maio, 1999).…”
Section: Introductionmentioning
confidence: 99%